2023
DOI: 10.3390/ijms24076452
|View full text |Cite
|
Sign up to set email alerts
|

Pyrogallol from Spirogyra neglecta Inhibits Proliferation and Promotes Apoptosis in Castration-Resistant Prostate Cancer Cells via Modulating Akt/GSK-3β/β-catenin Signaling Pathway

Abstract: Castration-resistant prostate cancer (CRPC) is an advanced form of prostate cancer associated with poor survival rates. The high proliferation and metastasis rates have made CRPC one of the most challenging types of cancer for medical practitioners and researchers. In this study, the anti-cancer properties and inhibition of CRPC progression by S. neglecta extract and its active constituents were determined using two CRPC cell lines, DU145 and PC3. The ethyl acetate fraction of S. neglecta (SnEA) was obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
0
0
Order By: Relevance
“…Previous studies demonstrate that a higher concentration of pyrogallol induces cytotoxicity in liver cancer cell lines like Hep G2 and HUH7 (Ahn et al, 2019). Another study report suggests that pyrogallol could enhance apoptosis by Modulating Akt/GSK-3β/β-catenin signaling Pathway in prostate cancer (Arjsri et al, 2023). In our subsequent study, we examined the effects of pyrogallol on aerobic glycolysis and found substantial results.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies demonstrate that a higher concentration of pyrogallol induces cytotoxicity in liver cancer cell lines like Hep G2 and HUH7 (Ahn et al, 2019). Another study report suggests that pyrogallol could enhance apoptosis by Modulating Akt/GSK-3β/β-catenin signaling Pathway in prostate cancer (Arjsri et al, 2023). In our subsequent study, we examined the effects of pyrogallol on aerobic glycolysis and found substantial results.…”
Section: Discussionmentioning
confidence: 77%